A comprehensive review on the lipid and pleiotropic effects of pitavastatin. (November 2021) - Sahebkar, Amirhossein; Kiaie, Nasim; Gorabi, Armita Mahdavi; Mannarino, Massimo R.; Bianconi, Vanessa; Jamialahmadi, Tannaz; Pirro, Matteo; Banach, Maciej
Abstract: The 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors, or statins, are administered as first line therapy for hypercholesterolemia, both in primary and secondary prevention. There is a growing body of evidence showing that beyond their lipid-lowering effect, statins have a number of additional beneficial properties. Pitavastatin is a unique lipophilic statin with a strong effect on lowering plasma total cholesterol and triacylglycerol. It has been reported to have pleiotropic effects such as decreasing inflammation and oxidative stress, regulating angiogenesis and osteogenesis, improving endothelial function and arterial stiffness, and reducing tumor progression. Based on the available studies considering the risk of statin-associated muscle symptoms it seems to be also the safest statin. The unique lipid and non-lipid effects of pitavastatin make this molecule a particularly interesting option for the management of different human diseases. In this review, we first summarized the lipid effects of pitavastatin and then strive to unravel the diverse pleiotropic effects of this molecule.